Is blood thicker than water? An analysis on the involvement of non-family members in family-owned firms listed in the Philippine Stock Exchange - Estomata, Renee Alysson (Animo Repository, 2021)
Family firms dominate a substantial portion of businesses worldwide. While there have been several dimensions used to explore the behavior of family firms, family involvement has been argued to overpower family ownership in its ability to influence firm performance. Despite existing literature on family involvement and firm performance, prior studies have been limited to the CEO position as a means to measure involvement. With this, the paper aims to investigate the influence of a non-family CEO and Chairman on the performance of publicly listed firms in the Philippines from 2008 to 2019 using the following metrics: Return on Assets, Return on Equity, and Tobin’s Q. With an unbalanced panel data set, the researchers aim to measure non-family involvement and firm performance using the two-step Blundell-Bond System Generalized Method of Moments (GMM) estimation technique to address possible issues of endogeneity. We find that non-family involvement is only significant when using Tobin’s Q as a measure of performance. With ROE as a measure, we find family ownership to be statistically significant with limited negative effects. Moreover, board duality, firm size, and tangibility were found to be significant depending on the performance measure used. Our results suggest that the impact of non-family involvement on firm performance is inconsistent.